Toxicity Assay of 2,4,5-Trimethoxybenzaldehyde Using Brine Shrimp Lethality Test (BSLT) - Lerrick, Reinner I.; Ximenes, Paskalia A.; Suwari, Suwari (Universitas Nusa Cendana, 2023)
Aromatic aldehydes including chalcones are known to have various biological activities. Such compound i.e. 2,4,5-trimethoxybenzaldehyde has also proven to be a COX-II inhibitor anti-inflammation and colon and breast cancer chemoprotective agent. This study aims to determine the toxicity of 2,4,5-trimethoxybenzaldehyde against artemia salina L. larvae according to the Brine Shrimp Lethality Test (BSLT) method. The results showed that the 2,4,5-trimethoxybenzaldehyde has a toxic effect with its LC50 is 70.12 µg/mL